2003
DOI: 10.1016/s0963-8695(03)00063-x
|View full text |Cite
|
Sign up to set email alerts
|

Observations of acoustic emission activity during gear defect diagnosis

Abstract: It is widely recognised that Acoustic Emission (AE) is gaining ground as a Non-Destructive Technique (NDT) for health diagnosis on rotating machinery. The source of AE is attributed to the release of stored elastic energy that manifests itself in the form of elastic waves that propagate in all directions on the surface of a material. These detectable AE waves can provide useful information about the health condition of a machine. This paper reports on part of an ongoing experimental investigation on the applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 10 publications
1
43
0
1
Order By: Relevance
“…High frequency (up to 1 MHz) impulsive and continuous-type components would therefore be expected. Amplitude, rms and ringdown counts all increased with defect size in e.g., [13], [23], [24] and it was also found that rms increased with misalignment of gears [27]. In these studies, sensors were placed upon gears or on the gearbox.…”
Section: Renewablesmentioning
confidence: 99%
“…High frequency (up to 1 MHz) impulsive and continuous-type components would therefore be expected. Amplitude, rms and ringdown counts all increased with defect size in e.g., [13], [23], [24] and it was also found that rms increased with misalignment of gears [27]. In these studies, sensors were placed upon gears or on the gearbox.…”
Section: Renewablesmentioning
confidence: 99%
“…Consequently, AE signals originating from any component other than the bearing will incur significant attenuation to an AE receiving sensor attached on the bearing housing. However, recent attempts [4] at locating the AE receiving sensor on rotating parts have been encouraging.…”
Section: Acoustic Emission In Rail Trackmentioning
confidence: 99%
“…Several maintenance methods for the diagnosis of damage to gear-teeth surfaces have already been developed using different techniques such as acoustic emission (Toutountzakis and Mba, 2003) (Miyachika, et al, 2006) and vibration (Haloui, et al, 2007) (Diwakar, et al, 2012) (Ohue, et al, 2011). However, it is still difficult to identify the location of the damage and provide a detailed estimate of its scale.…”
Section: Introductionmentioning
confidence: 99%